Continuity and Change in Criminal Offending by California Youth Authority Parolees Released 1965-1984 - Piquero, Alex R. ([Verlag nicht ermittelbar], 2001)
This research project used longitudinal data on 524 serious male juvenile offenders released from California Youth Authority (CYA) institutions from 1965-1984 to examine the relationship between changes in local life circumstances (marriage, employment, drug use, alcohol use, street time) and criminal offending. In particular, the project extended previous research on criminal careers by developing and applying an empirical model that accounted for the joint distribution of violent and nonviolent criminal offending by parolees in their late teens to mid-20s, during a newly recognized developmental period of the life course termed "emerging adulthood." The individuals were released from the CYA at various ages from the late teens to early 20s, but were all followed for a seven-year post-parole period. For each individual, the researchers obtained information on counts of criminal arrests as well as information on exposure time. Violent arrests included murder, rape, aggravated assault, robbery, and other person offenses such as extortion and kidnapping. Nonviolent arrests included burglary, receiving stolen property, grand theft, forgery, and grand theft auto. Within each year, individuals were coded as "free" for the number of months that they were not serving time in jail, prison, or CYA detention. Involvement of the following life circumstances was recorded: (1) alcohol use, (2) heroin use, (3) full-time employment, and (4) marriage. A "month-score" indicating how many months the parolee was employed full-time during the course of each of the seven years of observation was also recorded. Offenders were assumed to have maintained the same status unless a change was noted in the California Department of Corrections files. In addition, the researchers developed an index to gauge an offender's stake in conformity by combining the life circumstances of marriage and full-time employment. Variables in the data include year of follow-up, race, age during that year of follow-up, number of months not serving time, stake in conformity index score, and number of arrests for violent offenses, nonviolent offenses, and total offenses. Dummy variables are provided on alcohol use, heroin use, use of mind-altering drugs, use of uppers/downers, dependence on alcohol or heroin, marital status, common-law marriage, and employment.